MODELING IN PREDICTING ENTREPRENEURIAL INTENTION - Wibowo, Setyoningsih; Sijabat, Rauly; Widiastuti, Tri (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2025)
Job opportunities for college graduates are increasingly limited. On the other hand, the number of intellectual unemployment is increasing. The mindset of students who are still job seekers oriented rather than creating jobs (job creators) makes the imbalance between labor demand and supply worse. The study of the variable explanatory variables of entrepreneurial intention has been carried out, although the results are not conclusive and the involvement of mediating variable or the moderation is still limited. Finding and re-explaining variable that can explain the problem regarding the low entrepreneurial interest is a decent job to be examined again in this study. This study was conducted on final-level student respondents at accredited A colleges in Semarang through interviews by using questionnaires. The data obtained were analyzed using the Binary Logistic Regression Test. The results show that attitude and contextual factors are the variables that can explain the entrepreneurial interest clearly. The self-confidence variable is actually not able to moderate the influence of attitude and contextual factors on the entrepreneurial interest. This study also shows that autonomy and authority are dimensions that have dominant influence in explaining attitudinal factor and academic support is the dominant dimensions in explaining contextual factor.